Monte carlo investigation of spatially adaptable magnetic behavior in stretchable uniaxial ferromagnetic monolayer film - Laosiritaworn,Y. (The Korean Magnestics Society, 2015)
© The Korean Magnetics Society. All rights reserved. In this work, Monte Carlo simulation was employed to model the stretchable Ising monolayer film to investigate the effect of the spatial distance variation among magnetic atoms on magnetic behavior of the film. The exchange interaction was considered as functions of initial interatomic distance and the stretched distance (or the strain). Following Bethe-Slater picture, the magnetic exchange interaction took the Lennard-Jones potential-like function. Monte Carlo simulations via the Wolff and Metropolis algorithms were used to update the spin systems, where equilibrium and dynamic magnetic profiles were collected. From the results, the strain was found to have strong influences on magnetic behavior, especially the critical behavior. Specifically, the phase transition point was found to either increase or decrease depending on how the exchange interaction shifts (i.e. towards or away from the maximum value). In addition, empirical functions which predict how the critical temperatures scale with initial interatomic distance and the strain were proposed, which provides qualitatively view how to fine tune the magnetic critical point in monolayer film using the substrate modification induced strain.